Band Gap Reduction in Ferroelectric BaTiO3 Through Heterovalent Cu-Te Co-Doping for Visible-Light Photocatalysis - Rohj, Rohit Kumar; Hossain, Akmal; Mahadevan, Priya; Sarma, D. D. (Frontiers in Chemistry, 2021)
It is believed that ferroelectrics may serve as efficient photocatalysts as well as photovoltaic materials but for their large bandgaps which does not allow them to absorb a large part of the solar spectrum. We have explored theoretically within ab-initio density functional theory-based calculations, the efficacy of Cu and Te to co-dope BaTiO3 in reducing its bandgap while retaining its ferroelectric properties. Examining a dopant concentration of 11%, we find an insulating ground state being realized with a band gap reduction of 0.42 eV from the value for undoped BaTiO3 for some doping configurations. Ferroelectric distortions are found to survive even in the presence of doping suggesting possible applications in photocatalysis as well as photovoltaics.